Impact of First Eye Cataract Surgery on Quality of Life - Mayasari Wahyu Kuntorini; Maya Primagustya Achmad; Aldiana Halim (Majalah Kedokteran Bandung, 2023)
Cataracts are the second leading cause of visual impairment and the first cause of blindness, both globally and Indonesia. Cataracts do not only reduce vision but also the quality of life of the patients. Cataract surgery of at least one eye is expected to improve the patient's visual function and quality of life. This study aimed to assess the quality of life of patients with bilateral senile cataracts after the first eye surgery compared to people with normal vision. This was a cross-sectional study on 75 patients who underwent their first eye cataract surgery at the Cataract and Refractive Surgery Unit and 75 people with normal vision who visited the Refraction, Contact Lens, and Low Vision Unit of the National Eye Center of Cicendo Eye Hospital during the period of March-June 2020. The quality of life assessment was conducted through interviews using the National Eye Institute Visual Function Questionnaire-25. The non-inferiority test with a margin of 20% was performed. The mean age of the subjects was 63.49 years with no difference in the proportion of gender. Presenting visual acuity of binoculars after the first cataract surgery was 0.26 LogMAR and normal vision was 0.07 LogMAR. With a margin of 20%, the patient's quality of life after the first cataract surgery was not inferior to the normal vision subjects (d = -2.45% (95% CI -6.3% to 1.4%).) Hence, patients' quality of life after the first cataract surgery is not inferior to those with normal vision.